2016
DOI: 10.1089/apc.2015.0213
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Metabolic Syndrome and Cardiovascular Disease Risk Among People with HIV on Stable ART in Southwestern Uganda

Abstract: The objectives of this study were to determine the epidemiology and correlates of cardiovascular disease (CVD) risk among Ugandans on first-line antiretroviral therapy (ART). We conducted a cross-sectional study at an HIV clinic in southwestern Uganda. We enrolled adult patients on non-nucleoside-based ART regimens for a minimum of 2 years. We collected anthropometric and clinical measurements, smoking history, and blood for fasting lipid profile and blood sugar (FBS). Outcomes of interest were (1) presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 43 publications
10
63
0
4
Order By: Relevance
“…Consistent with other studies, we found a low prevalence of hyperglycemia (3.4%) [2426], which was not affected by ART regimen [27] but significantly affected by increasing age [28]. The prevalence of abdominal obesity in our study is comparable to the 30% observed in a Southwestern Ugandan ART cohort [26] but was lower than that reported in the background GPC population-56% [10]. High prevalence of obesity among women than men has also been previously established by studies in SSA (24-26) and Europe [29].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies, we found a low prevalence of hyperglycemia (3.4%) [2426], which was not affected by ART regimen [27] but significantly affected by increasing age [28]. The prevalence of abdominal obesity in our study is comparable to the 30% observed in a Southwestern Ugandan ART cohort [26] but was lower than that reported in the background GPC population-56% [10]. High prevalence of obesity among women than men has also been previously established by studies in SSA (24-26) and Europe [29].…”
Section: Discussionsupporting
confidence: 93%
“…A recently published single‐centre study in Uganda with a sample size of 250 patients found an aOR of 1.67 for MetS in patients on AZT/3TC/NVP as compared to TDF/3TC/EFV. The finding was, however, not significant, and the analysed subgroups were small (129 in TDF and 68 in AZT group) .…”
Section: Discussionmentioning
confidence: 74%
“…A recently published single-centre study in Uganda with a sample size of 250 patients found an aOR of 1.67 for MetS in patients on AZT/3TC/NVP as compared to TDF/3TC/EFV. The finding was, however, not significant, and the analysed subgroups were small (129 in TDF and 68 in AZT group) [17]. With near-normal life expectancies among PLWHA taking ART and increasing age of patients on ART, cardio-vascular risk factors in PLWHA gain considerable importance.…”
Section: Discussionmentioning
confidence: 88%
“…[14] The prevalence of diseases related to altered glucose and fat metabolism, including diabetes and cardiovascular disease, has also continued to increase among PLWH in the United States. A longitudinal study of insulin resistance (IR) in PLWH on newer ART regimens identified IR in 21% of participants, which represents a significant decrease from estimates of 35–63% prevalence IR with older ART regimens.…”
Section: Metabolic Complications Are Increasing Among People Living Wmentioning
confidence: 99%